Factors Of Service Quality Affecting Customer Satisfaction Of Mobile Banking Users At Pt. Bank Sumut Kc Siantar, North Sumatra - Ningtias Aprili Maliyah; Nurul Jannah; Nurbaiti Nurbaiti (UNIVERSITAS PAKUAN, 2025)
. The purpose of this paper is to explore the influence of Responsiveness, Reliability, and Assurance on The purpose of this paper is to explore the influence of Responsiveness, Reliability, and Assurance on the level of customer satisfaction at the Siantar Branch Office (KC) of PT. Bank of North Sumatra. This research approach adopts a quantitative method with data collection through observation and the use of questionnaires. The sample consisted of 90 respondents from PT. Bank of North Sumatra KC Siantar. Data analysis was carried out using SPSS Version 25 software, by applying descriptive analysis, multiple regression, hypothesis testing, and determination coefficients. The results of the partial test show that Reliability, which is also partially proven to have a positive and significant influence on customer satisfaction of 0.204. The influence of Assurance has a positive and significant influence on the level of customer satisfaction, which is 0.242 Likewise, the influence of responsiveness has a positive and significant influence on the level of customer satisfaction, which is 0.228.. In addition, t-test testing shows that partially, it can be concluded that Assurance significantly affects customer satisfaction, so the hypothesis is acceptable. Overall, the variables Reliability, Assurance and Responsiveness together contribute positively and significantly to the level of customer satisfaction at PT. Bank of North Sumatra KC Siantar at 72.7%. Keywords: Servqual, Resvonsivenes, Reability, Assurance and Customer Satisfaction